2016
DOI: 10.1073/pnas.1600400113
|View full text |Cite
|
Sign up to set email alerts
|

Salinity of deep groundwater in California: Water quantity, quality, and protection

Abstract: Deep groundwater aquifers are poorly characterized but could yield important sources of water in California and elsewhere. Deep aquifers have been developed for oil and gas extraction, and this activity has created both valuable data and risks to groundwater quality. Assessing groundwater quantity and quality requires baseline data and a monitoring framework for evaluating impacts. We analyze 938 chemical, geological, and depth data points from 360 oil/gas fields across eight counties in California and depth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 38 publications
1
57
0
1
Order By: Relevance
“…The century-and-a-half-long history of oil and gas development in Pennsylvania and other US states, such as Texas and California, has resulted in millions of abandoned wells, and in many cases, poorly documented or missing well records (3,(9)(10)(11). As a result, there is a lack of data to characterize abandoned oil and gas wells and the possible relationship between methane emissions and well attributes.…”
mentioning
confidence: 99%
“…The century-and-a-half-long history of oil and gas development in Pennsylvania and other US states, such as Texas and California, has resulted in millions of abandoned wells, and in many cases, poorly documented or missing well records (3,(9)(10)(11). As a result, there is a lack of data to characterize abandoned oil and gas wells and the possible relationship between methane emissions and well attributes.…”
mentioning
confidence: 99%
“…SETS approaches have also been recently applied (or proposed) for reducing the impacts of drought in California. Technologically oriented options being implemented or explored include desalination (such as the 50 million gallons per day Carlsbad Desal Plant near San Diego), groundwater drilling, and wastewater recycling (Cooley et al, ; Gorman, ; Howard & Millsap, ; Kang & Jackson, ; McKenzie, ; San Diego County Water Authority, ; Underwood, ). Ecologically based solutions include the use of more native vegetation in landscaping and the implementation of fog harvesting systems inspired by nature (California Water Service, ; FogNet, ; Goldstein, ; Knickmeyer, ; Weiss‐penzias et al, ).…”
Section: Using a Sets Lens To Move Beyond Technologically Focused Resmentioning
confidence: 99%
“…Algae Growth = +0.050 −3.000E-003 × A +3.000E-003 × B −0.020 × C + 3.750E-003 × AB −3.750E-003 × AC +3.750E-003 × BC −9.545E-003 × A 2 −9.545E-003 × B 2 +0.015 × C 2 Final equation in terms of actual factors: Microalgae Growth = +0.090273 +3.51818E-004 × COD +2.61818E-003 × TDS −0.81818 × Microalgae Absorbance +3.75000E-006 × COD × TDS −3.75000E-004 × COD × Microalgae Absorbance + 3.75000E-003 × TDS × Microalgae Absorbance −9.54545E-007 × COD 2 −9.54545E-005 × TDS 2 +1.54545 × Microalgae Absorbance 2 The results obtained in this work are similar to some of the previous observations using process optimization techniques [49]. In this study, we noticed the interaction and quadratic effects to be significant as reported in other studies focusing on microbial fuel cells [42,[50][51][52][53][54].…”
Section: Microalgae Growth Final Equation In Terms Of Coded Factorsmentioning
confidence: 99%